A novel vertical SCR for ESD protection in 40 V HV bipolar process. (November 2017) - Liu, Fan; Liu, Zhiwei; Liu, Jizhi; Cheng, Hui; Zhao, Liu; Tian, Rui; Song, Shiyu; Liou, Juin J.
Abstract: A vertical Silicon Controlled Rectifier (VSCR) realized in a high-voltage (HV) 40 V bipolar process is proposed for electrostatic discharge (ESD) protection applications. In addition, a new method is proposed to alter the layout of the emitter regions of the parasitic vertical PNP (VPNP) bipolar transistor in the VSCR to optimize the trigger voltage and the area of the VSCR. The transmission line pulsing (TLP) measurement results show that the VSCR possesses enhanced ESD robustness compared to the conventional vertical PNP (VPNP) bipolar transistor. The new VSCR can adjust trigger voltage, holding voltage and failure current with changing the number of emitter regions. Compare to VPNP bipolar transistor, the VSCR is more suitable for 40 V bipolar process. Highlights: The new VSCR can be constructed by only changing the electrode connection of the VPNP bipolar transistor. The VSCR's topology was further optimized by using different emitter region and finger numbers. The VSCR is small snapback, high robustness, large holding voltage, and small on-state resistance. Compared with VPNP, the layout area of VSCR is reduced more than 90% with the equal failure current.